Antifungal activity of the ethanolic extracts of Punica granatum L. and evaluation of the morphological and structural modifications of its compounds upon the cells of Candida spp. - Anibal,Paula Cristina (2013)
Ethanolic crude extracts prepared from the arils and seeds, pericarp, peels and from the whole fruit of Punica granatum, known as pomegranate, had their antifungal activity tested against Candida spp. The ethanolic crude extracts were analyzed by Mass Spectrometry and yielded many compounds such as punicalagin and galladydilacton. The extracts from the pericarp and peel showed activity against Candida spp., with MICs of 125 µg/mL. The effect of pericarp and peel extracts upon the morphological and structure of C. albicans and C. krusei were examined by scanning and transmission electron microscopy, with the visualization of an irregular membrane and hyphae, formation of vacuoles and thickening of the cell wall. The data obtained revealed potential antimicrobial activity against yeasts cells of the Candida genus, and the bioactive compounds could be responsible for changes in cell morphology and structure. The data obtained open new perspectives for future research in continuation to this study, where information such as determination of the site of action of the compounds could contribute to an alternative therapy against these organisms.